Low emission zones and population health - Shushanik Margaryan (University of Hamburg, Hamburg Center for Health Economics (HCHE), 2019)
Air pollution has a major detrimental impact on population health but little is known about the effectiveness of policy measures targeting pollution. I exploit the staggered implementation of low emission zones in large cities in Germany as a nat-ural experiment to asses their health impact. Using outpatient and inpatient health care data, I demonstrate that low emission zones reduce the number of patients with cardiovascular diagnoses by 2-3 percent. This effect is particularly pronounced for the elderly above 65.
Keywords: 330